2019
DOI: 10.1016/j.ecolind.2019.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of DNA metabarcoding and morphological identification for stream macroinvertebrate biodiversity assessment and monitoring

Abstract: Conventional morphology-based identification is commonly used for routine assessment of freshwater ecosystems. However, cost and time efficient techniques such as high-throughput sequencing (HTS) based approaches may resolve the constraints encountered in conducting morphology-based surveys. Here, we characterized stream macroinvertebrate species diversity and community composition via metabarcoding and morphological analysis from environmental samples collected from the Shigenobu River Basin in Ehime Prefectu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 65 publications
(69 reference statements)
4
47
1
Order By: Relevance
“…The overall taxonomic composition obtained from genetic and morphological data reveals a distinct intra-lake diatom distribution pattern in the investigated localities of the large and heterogenous Lake Bolshoe Toko. Both approaches largely overlap in beta diversity estimations, whereas we find large differences in the taxonomic assignment and richness of identified taxa, similar to that reported in studies on stream invertebrates [57] or seagrass communities [58]. In our data, the families Fragilariacaea and Aulacoseiraceae are abundant and rich according to both approaches, but the genetic dataset does not uncover the abundance and diversity within the family Stephanodiscaceae and Achnanthaceae.…”
Section: Genetic and Morphological Pattern Of Diatom Diversity Withinsupporting
confidence: 80%
“…The overall taxonomic composition obtained from genetic and morphological data reveals a distinct intra-lake diatom distribution pattern in the investigated localities of the large and heterogenous Lake Bolshoe Toko. Both approaches largely overlap in beta diversity estimations, whereas we find large differences in the taxonomic assignment and richness of identified taxa, similar to that reported in studies on stream invertebrates [57] or seagrass communities [58]. In our data, the families Fragilariacaea and Aulacoseiraceae are abundant and rich according to both approaches, but the genetic dataset does not uncover the abundance and diversity within the family Stephanodiscaceae and Achnanthaceae.…”
Section: Genetic and Morphological Pattern Of Diatom Diversity Withinsupporting
confidence: 80%
“…Previous studies have shown the great potential of metabarcoding for biotic assessments in various contexts, including Malaise trap surveys (Morinière et al, ), biosurveillance of invasive and pest species (Ashfaq & Hebert, ; L. A. Hardulak et al in prep), macrozoobenthos sampling for assessing water and stream health (Elbrecht & Leese, ; Serrana, Miyake, Gamboa, & Watanabe, ), faeces analyses for dietary inference (De Barba et al, ; Hawlitschek, Fernández‐González, Balmori‐de la Puente, & Castresana, ), species identification for forensic entomology (Chimeno et al, ) and for soil biology (Oliverio, Gan, Wickings, & Fierer, ). This approach combines the advantages of DNA barcoding, namely the capacity to identify any life stage, body fragment or even trace DNA in the environment, with the ability of high‐throughput sequencers to analyse millions of DNA fragments and thousands of specimens at a time.…”
Section: Discussionmentioning
confidence: 99%
“…Biodiversity assessment and ecosystem monitoring require accurate measures of community composition to address environmental comparisons and identify negative anthropogenic impacts (Hillebrand et al, 2018;US Environmental Protection Agency, 2011). In aquatic systems, macroinvertebrates commonly comprise a focal group for biomonitoring, due to their high diversity and range of responses to environmental conditions (Menezes, Baird, & Soares, 2010;Resh, Norris, & Barbour, 1995). However, current biomonitoring methods often have coarse taxonomic resolution leading to false negatives for rare or cryptic macroinvertebrate taxa (Haase et al, 2006;Pfrender et al, 2010) and frequently miss important differences between closely related species (Macher et al, 2016).…”
Section: Edna and Metabarcoding In Environmental Assessmentsmentioning
confidence: 99%